2016
DOI: 10.1016/j.robot.2016.08.021
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical reinforcement learning as creative problem solving

Abstract: h i g h l i g h t s • Reinforcement learning's option switches are analogous to psychological insight. • Insight and options reveal comparable capabilities for transformational creativity. • Open problems remain: lifelong learning, switching when exploring, option discovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 56 publications
0
13
0
Order By: Relevance
“…Likewise, agents need to explore the environment to find more optimal solutions. A first approach of combining creativity with reinforcement learning shows that creativity offers the potential to explore promising solution spaces whereas traditional methods fail (Colin et al, 2016). We encourage researchers to build upon recent prosocial behaviour studies to deepen our understanding of efficient coordination.…”
Section: Psychologymentioning
confidence: 99%
“…Likewise, agents need to explore the environment to find more optimal solutions. A first approach of combining creativity with reinforcement learning shows that creativity offers the potential to explore promising solution spaces whereas traditional methods fail (Colin et al, 2016). We encourage researchers to build upon recent prosocial behaviour studies to deepen our understanding of efficient coordination.…”
Section: Psychologymentioning
confidence: 99%
“…Several authors suggested that modern reinforcement learning algorithms based on MDPs could allow simulation of the creative process in autonomous agents ( Vigorito and Barto, 2008 ; Schmidhuber, 2010 ; Colin et al, 2016 ). Reinforcement learning (RL) resembles the creative process as both involve interaction between a decision-making agent and its dynamic, uncertain environment, when the agent is searching for a solution to a given problem.…”
Section: Creative Processes In Autonomous Robotsmentioning
confidence: 99%
“…This information is used to deduce an optimal policy ( Kober et al, 2013 ). According to Colin et al (2016) , the agent’s policy changes within hierarchical reinforcement learning algorithms resemble the change in strategies that happens during creative processes.…”
Section: Creative Processes In Autonomous Robotsmentioning
confidence: 99%
“…Instead of autonomously creating novel options, Konidaris et al ( 2011 ) extended this approach by deriving options from segmenting trajectories trained by demonstration. On a more abstract level, Colin et al ( 2016 ) investigated creativity for problem-solving in artificial agents in the context of hierarchical reinforcement learning by emphasizing parallels to psychology. They argue that hierarchical composition of behaviors allows an agent to handle large search spaces in order to exhibit creative behavior.…”
Section: Related Workmentioning
confidence: 99%